The Effect of 3T School Digitalization in the Era of the COVID-19 Pandemic - Ana Silfiani Rahmawati; Daniel Wolo (Postgraduate, University of Mataram, 2022)
This study aims to determine whether digitizing 3T schools in the era of the covid 19 virus pandemic. The type of research used is survey research using quantitative descriptive analysis. The research design is Ex-Post Facto. The subjects in this study are schools included in the 3T region (frontier, outermost, and underdeveloped) in Indonesia, especially in the East Nusa Tenggara region. The object of this study was 40 3T school teachers in four districts on the island of Flores (Nagakeo Regency, East Manggarai Regency, Manggarai Regency, and West Manggarai). The results showed that the number of respondents who answered in the agree category got the highest number, namely 19 people with a percentage of 47%. In the strongly agree category, there were 16 people with a percentage of 40%, the category did not agree. Five people with a percentage of 13%, and none. Who chose the category strongly disagree (percentage 0%). From this, it can be concluded that school digitization has a positive effect during the COVID-19 pandemic; this can be seen from the number of teachers in the 3T region who chose the agreed category, namely 19 people (47%)